The impact of residual varus alignment following total knee arthroplasty on patient outcome scores in a constitutional varus population - Lanting, Brent A.; Williams, Harley A.; Matlovich, Nicholas F.; Vandekerckhove, Pieter-Jan; Teeter, Matthew G.; Vasarhelyi, Edward M.; Howard, James L.; Somerville, Lyndsay E. (The knee, 2018)
Following a total knee arthroplasty (TKA), restoration of the mechanical axis of the lower limb to a neutral position of 0° ± 3° is generally considered the standard of care. Little is known, however, regarding the impact of realignment defined according to the patient's physiologic anatomy on clinical outcome scores. The study included 67 knees with a mean age of 65.9 ± 8.3 years with unilateral osteoarthritis (OA) who underwent a primary unilateral TKA for medial end-stage OA. Patients were categorized based on post-operative limb alignment in one of two ways, either based on alignment relative to their contralateral, physiologic side (physiologic), or alignment relative to a neutral axis (neutral). Knee Society Score (KSS), Western Ontario & McMaster Universities Osteoarthritis Index (WOMAC), and the 12-Item Short Form Survey (SF-12) were compared between the two groups. WOMAC Total and subscale scores improved for both groups between the pre- and post-operative time points. SF-12 scores were comparable post-operatively between the groups. WOMAC and KSS total and subscale scores were slightly greater post-operatively in the group not aligned according to their physiologic anatomy (neutral). However, none of these differences reached a level of significance. Post-operatively, residual varus and neutral limb alignment lead to comparable clinical outcome scores. In a constitutional varus population with medial end-stage OA, aligning the lower limb during a TKA to a neutral position rather than the patient's native anatomy does not negatively impact self-reported patient outcome scores at the one and two-year time points.